Factors associated with body weight status among students in infrastructure University Kuala Lumpur (IUKL), Kuala Lumpur, Malaysia - K. Mahgoub, Salma; Abu Saad, Hazizi; Jamaluddin, Rosita (IGM Publication, 2016)
The occurrence of obesity and overweight status in the population has caught public attention. This is in line with the World Health Organization's concern (2013). The present study aimed to determine factors associated with body weight status among students in Infrastructure University Kuala Lumpur (IUKL), Kuala Lumpur, Malaysia. A cross-sectional study was conducted to asses physical activity level, environmental factors affecting physical activity level and their association with body weight status among 280 students in Infrastructure University Kuala Lumpur (IUKL), Kuala Lumpur, Malaysia. The mean of respondent’s total physical activity per week was 3988.50 ± 6758.45 METs minute/week. This was significantly higher (t = 3.020, p = 0.003) among male respondents (5496.37 ± 7860.26 METs minute/week) compared to females (3032.93 ± 5779.55 METs minutes/week). The overall environmental supports for physical activity among the respondents were at moderate level (2.17 ± 0.72), although the total environmental supports for physical activity among female is slightly higher compared to male (2.17 ± 0.77 vs 2.15 ± 0.63), no significant different was observed (t = - 0.25; p = 0.805). In general over weight / obese status was highly prevalent among those with low involvement with neighbourhood environment for physical activity (28%) (the lowest quartile). Although adjusted crude analysis of support to neighbourhood environment for physical activity showed reverse associations with overweight / obese status, no significant trend was observed.